THE PROFILE OF LIFE QUALITY AND THE FLEXIBILITY ON THE GROWING OLD PROCESS (Fiep Bulletin - online, 2014)
It was opted to this type of research with the objective to investigate the profile of the quality of life and the flexibility of individuals with equal or superior age the 65 years. In this direction the research comes to justify itself, for the importance of if verifying this component of the physical aptitude that mainly has great importance for the health of the third age, therefore this 0 variable influences of negative form the quality of life. This research if characterized as a descriptive study. The sample was constituted by 23 individuals being 16 of feminine sex and 7 of the masculine sex, with equal or superior age the 65 years, that are part of the group ofconjuncts of the church of Corumbá-GO. It applied test to seat and to reach of the bank of Wells, a questionnaire; quality of life - WHOQOL bref. The results will be presented in the form standard of analyze descriptive with shunting line standard of the data inagreement picture 1. The joined results form: The level of quality of life, the sample in the generality presented classification 12,95 (2,82) that it is considered as nor bad and nor good. How much to the 4 domínios (physicist, psychological, social relations and environment), the domain environment is only that the two sexos had been different, therefore the aged women is very unsatisfied, while the men consider this bad and nor good aspect as nor; How much to the level of flexibility without no previous repetition it presented one average of 15,30 cm (9,55), already the test of flexibility with 4 repetitions, presented a average of 18,13 cm (10,12), being classified the level of flexibility as average for the sample in the generality. When analyzed for sex, the feminine one it had a flexibility between good medium and, while the masculine sex was classified as weak. One concludes that in both the sexos, the study evidenced that in the analysis of the quality of life in the generality, the aged ones had presented a perception of nor bad and nor good.How much to the level of flexibility of the sample in the generality it presented an average level, the feminine sample had a positive index, being that the masculine sample did not get a satisfactory result, having as classification the weak level.
Keywords: Aging; Flexibility; Quality of life.